Hedging with Futures: Does Anything Beat the Naïve Hedging Strategy? - Wang, Yudong; Wu, Chongfeng; Yang, Li (Management science, 2015)
This paper investigates out-of-sample performance of the naïve hedging strategy relative to that of the minimum variance hedging strategy, in which the covariance parameters are estimated from 18 econometric models. Hedging performance is compared across 24 futures markets. Our main findings suggest that it is difficult to find a strategy under the minimum variance framework that outperforms the naïve hedging strategy both consistently and significantly. Our findings are robust to different sample periods, estimation windows, and hedging horizons and can be partly explained by the effects of estimation error and model misspecification. Data, as supplemental material, are available at http://dx.doi.org/10.1287/mnsc.2014.2028 . This paper was accepted by Itay Goldstein, finance.